Microbiological and Antibiogram Profiling of Frozen Foods and Ice Cream Products from Super-Shops of Dhaka, Bangladesh (Stamford Journal of Microbiology, 2024)
The current study was conducted to assess the microbiological loads and antibiotic resistance patterns among 20 frozen food and ice cream samples that were gathered from multiple super-shops in Dhaka, Bangladesh. A total of 20 samples (11 frozen food samples and 9 ice cream samples) were collected from different supershops in Dhaka, Bangladesh during the period from July 2024 to September 2024. Microbiological analyses were performed to determine the total viable bacterial count (TVBC), total coliform count (TCC), and total staphylococcal count (TSC). The highest total viable bacterial count (2.12×109 cfu/g), highest coliform count (3.7×107 cfu/g), and highest staphylococcal count (2.04×108 cfu/g) were found in the frozen fish sample. Bacteria were isolated and identified based on their morphological and biochemical characteristics. While E. coli and Klebsiella spp. were observed in seven samples, Staphylococcus aureus was identified in twelve. Additionally, different antimicrobial agents were used to determine the isolates' susceptibility towards them. Ciprofloxacin, Imipenem, and Gentamicin have been demonstrated to be the most effective drugs against each isolate. All of the Klebsiella isolates exhibited sensitivity to Chloramphenicol, whereas most of the E. coli isolates were sensitive to Erythromycin, Chloramphenicol, and Nalidixic acid. However, erythromycin and amoxicillin were found to be less effective against Staphylococcus aureus isolates. The presence of several different microorganisms suggests that the majority of frozen food samples did not meet public health standards. These frozen foods, contaminated with multi-antibiotic-resistant microorganisms, have the potential to transmit food-borne diseases.Stam. J. Microbiol. 2024; 14(1): 22-27